Edukasi Osteoarthritis Lutut Pada Komunitas Lansia di Posyandu Lansia Timuran Setabelan Surakarta - Evita Sari; Isnaini Herawati; Yusuf Arianto (Universitas 45 Surabaya, 2024)
Osteoarthritis is one of the contributors to the state of living with musculoskeletal disability. Because osteoarthritis is more common in older people with a typical onset of the age of 40-60 years. Although there are some cases of adolescents or athletes experiencing osteoarthritis. Data at the physiotherapy poly at the Setabelan health center is obtained per month there are 28 cases and per year 246 cases come to the physiotherapy room. This is only a case recorded and reported at the same health center, while according to Osteoarthritis data in Indonesia reaches 65% of the entire number of elderly in Indonesia. This data shows that osteoarthritis sufferers are still high and even occupy the peak of conditions suffered by the elderly in Indonesia. Efforts to prevent and control osteoarthritis knee disorders must be intensified again among the elderly in the same area. Through counseling at every elderly posyandu in the setabelan area, Surakarta. In the community, especially the elderly, can find out activities that worsen complaints and activities that can reduce complaints of knee osteoarthritis